Pengaruh Kepuasan Kerja Terhadap Semangat Kerja Pegawai Dinas Kependudukan dan Pencatatan Sipil Kabupaten Ogan Ilir - Lusri Indrawaty; Zunaidah Zunaidah; Parama Santati (Transformasi Manageria: Journal of Islamic Education Management, 2024)
This study aims to analyze the effect of job satisfaction on work spirit of employees in the Population and Civil Registration Office of Ogan Ilir Regency. The populations in this study were all employees of the Population and Civil Registration Office of Ogan Ilir Regency. This research used saturation sampling method, for 58 respondents. The data in this study were collected using a questionnaire method. The analysis technique used was simple linear regression analysis. Based on the results of the analysis, it was concluded that job satisfaction had a positive and significant effect on work spirit of employees of the Population and Civil Registration Office of Ogan Ilir Regency. Keywords: Job Satisfaction, Work Spirit